Development and Test of the 1 700 V/2 400 A IGBT Module for Wind Power Converter - LI Xin; FANG Jie; NING Xubin; YU Wei (Kongzhi Yu Xinxi Jishu)
Converter plays a key role in wind power systems. As the basic part of a converter, power electronic devices determine its performance and reliability, and are the key factors to decide if the wind power turbine can operating stable and reliable for longtime. This paper mainly introduced the chip performances and module design of CRRC’s 1 700 V/2 400 A IGBT, and its high suitability for wind power converter use. It also presented the IGBT dynamic test results and power test results that applied to power assembly. Dynamic and static test results show that the module has a good balance between losses and softness of module, lower overshoot voltage within the safe working area of RBSOA.